Respuesta :
Answer:
x=-8,y=-48
Step-by-step explanation:
[tex]y=3x-24\\5x-y=8\\Hence,\\y=3x-24\\-y=-5x+8\\By\ adding\ the\ system\ of\ equations\ we\ get,\ \\y+-y=3x-24+(-5x+8)\\0=3x-24-5x+8\\5x-3x=-24+8\\2x=-16\\x=-8\\So,\\Substituting\ x=-8\ in\ the\ first\ equation\ we\ get,\ \\y=3*-8-24\\y=-24-24\\y=-48[/tex]
Answer:
x = - 8
y = - 48
Step-by-step explanation:
Here, y = 3x - 24 and 5x - y = 8 is given
So, First name the equation
y = 3x - 24 ...(1)
5x - y = 8 ...(2)
Now, Put the value of y in equation (2) we get
5x - y = 8
5x - (3x - 24) = 8
5x - 3x + 24 = 8
2x = 8 - 24
2x = -16
x = -16÷2
x = - 8
Here, we get the value of x in equation (1)
y = 3x - 24
y = 3(- 8) - 24
y = - 24 - 24
y = - 48
FOR VERIFICATION ONLY:
y = 3x - 24
-48 = 3(-8) - 24
-48 = -48
5x - y = 8
5(-8) -(- 48) = 8
-40 + 48 = 8
8 = 8
Hence, L.H.S = R.H.S
-TheUnknownScientist